The Effects of Mathematics Learning Management on Multiplication of Multi-Digit Numbers by Two-Digit Numbers through Game-based learning in 99 Math Website of Fourth Grade Students - ชมภูราช ประภาพรรณ; ภู่ทอง อนุสรา; คล้อยสวาท เกศมณี; ชาวระนอง ชัยยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) compare the academic achievement on multiplication of more than 2 digits with 2 digits before and after learning using a game-based learning in the 99 Math website of fourth grade students and 2) study the learning retention after using a game-based learning in the 99 Math website of fourth grade students. The sample group consisted of 43 fourth grade student, class 1 of St. Peter’s School. The sample of this research was random sampling using the cluster sampling method. The research instruments were a game-based learning management plan, an achievement test, and learning retention test. The statistics used for testing the hypothesis were the t-test (Dependent Sample). The research results found that 1) students who participated on multiplication of more than 2 digits with 2 digits using a game-based learning in the 99 Math website had higher academic achievement scores after learning than before learning at a statistical significance level of .05. And 2) students who participated on multiplication of more than 2 digits with 2 digits using a game-based learning in the 99 Math website had a learning retention score after 2 weeks of learning, that was not significantly different from the score immediately after learning at the .05 statistical level.